Reviews (Modern theology, 1989)
Book reviewed in this article: R.S, Thomas: Poet of the Hidden God, by D.Z. Phillips, Macmillan The Methods of Modern Tehology by Paul Avis, Marshall Pickering Philosophy and Miracle: The Contemporary Debate, By David Basinger and Randall Basinger. Jesus In Our Western Culture: Mysticism, Ethics and Politics, by Edward Schillebeeckx. Believer, Christian, Catholic: Three Essays in Fundamental Theology by David Coffey, Catholic Institute of Sydney English-Speaking justice by George Parkin Grant, Notre Dame Judaism by Nicholas de Lange, Oxford University The Making of Modern German Christology from the Enlightenment to Pannenberg, by Alister E. McGrath Being As Communion by John D. Zizioulas. Darton, Longman The Form of Transformed Vision: Coleridge and the Knowledge of God by James S. Cutsinger Persons and Personality by A. Peacocke & G. Gillett